ANALISIS IMPLEMENTASI PROGRAM TERPADU PEMBERDAYAAN MASYARAKAT BERSPEKTIF GENDER DI KOTA SEMARANG - Saleh, Teguh Rahmat; Subowo, Ari; Rostyaningsih, Dewi (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
Implementation of Empowerment programs implemented by the Government of Semarang through the Integrated Program for Community Empowerment Gender-Based (P2MBG) encountered some resistance among communication factors, resources, characteristics of the implementing agency and culture so that the inhibiting factors must be addressed.